Optimization Of The National Zakat Amil Agency In Efforts Of Distributing Zakat Funds - Ahmad Iqbal; Yusdani (Islamic Business and Management Journal, 2023)
Education is one of the development sectors of the Indonesian nation to advance society in forming intellectual human resources. Contributions in the field of education are very important to be considered by the government in order to develop educational facilities and infrastructure for the people of Indonesia. The use of zakat funds in the long term is the solution for poor children in terms of education. Even so, it turns out that there are still many people who have not been touched by educational assistance through zakat. Therefore, BAZNAS is expected to be able to touch on this issue through its program, namely Sleman Smart. This research was carried out in 4 different places, namely at the BAZNAS Sleman Office, SD Negeri Perumnas 3, MTs N 4, and MAN 5 Sleman. The research method used is a qualitative method with a juridical-normative and sociological approach. The results of this study are the distribution of zakat funds at BAZNAS Sleman with 5 work programs. The 5 work programs consist of: Productive Sleman, Healthy Sleman, Smart Sleman, Careful Sleman and Taqwa Sleman. Another form that is carried out by the Sleman National Amil Zakat Agency (BAZNAS) is by using the muzakki route by awakening the muzakki themselves. BAZNAS Sleman also coordinates with Islamic organizations such as Nahdatul Ulama and Muhammadiyah so that there is no overlap between one another. Specifically, the Sleman Smart program was carried out in coordination with the education office and also the social service. Technical optimization of the National Amil Zakat Agency in this program consists of planning, organizing, collection and supervision. Another result is the distribution of zakat in the education sector in the form of cash distributed to underprivileged students (poor people). This program is expected to exist by students who need it.